2020
DOI: 10.1111/fire.12231
|View full text |Cite
|
Sign up to set email alerts
|

Institutional trading, investor sentiment, and lottery‐like stock preferences

Abstract: This paper explores the time-varying institutional investor preference for lottery-like stocks. On average, institutional investor holdings reflect an aversion to lottery-like stocks. However, I find that an institutions' aversion to lottery-like stocks is reduced when investor sentiment is low. Moreover, I find that during low sentiment periods, institutional investors have abnormally high trading profits in more positively skewed stocks. These results suggest that institutions reduce their aversion toward lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Second, this study contributes to the growing literature studying the relationship between gambling and financial decision‐making (e.g., Alldredge, 2020; Maung et al., 2020). Studies cross‐sectionally link gambling and sensation‐seeking to higher portfolio turnover (Dorn & Sengmueller, 2009; Grinblatt & Keloharju, 2009), a preference for lottery stocks (Doran et al., 2012; Kumar, 2009), and more active positions on household balance sheets (Li, 2012).…”
Section: Introductionmentioning
confidence: 87%
“…Second, this study contributes to the growing literature studying the relationship between gambling and financial decision‐making (e.g., Alldredge, 2020; Maung et al., 2020). Studies cross‐sectionally link gambling and sensation‐seeking to higher portfolio turnover (Dorn & Sengmueller, 2009; Grinblatt & Keloharju, 2009), a preference for lottery stocks (Doran et al., 2012; Kumar, 2009), and more active positions on household balance sheets (Li, 2012).…”
Section: Introductionmentioning
confidence: 87%
“…Li et al (2018) showed that funds as a whole are averse to gambling, but the proportion of shares of lottery-type stocks held by funds varies widely, and some funds actually have a strong gambling preference. Alldredge (2020) found that institutional investors increase their exposure to lottery-type stocks during periods of low market sentiment to trade ahead of individual investors and profit from the subsequent rise in stock prices as market sentiment improves.…”
Section: Heterogeneity In Investor Gambling Preferencesmentioning
confidence: 99%
“…Gompers and Metrick (2001) find that temporal demand shocks, rather than informed trading of institutional investors, positively predict future returns. More recently, whereas Lewellen (2011) shows that the aggregate institutional portfolio has overall performed poorly since 2000, Alldredge (2020) presents evidence that institutional investors generate abnormally high trading profits in lottery‐like stocks during low‐sentiment periods.…”
Section: Introductionmentioning
confidence: 99%